2020
DOI: 10.1371/journal.pone.0231972
|View full text |Cite|
|
Sign up to set email alerts
|

Hydrogen extends Caenorhabditis elegans longevity by reducing reactive oxygen species

Abstract: At present, a large number of studies have reported that hydrogen has antioxidant functions and prevents oxidative stress damage. However, it is not clear whether hydrogen can prolong longevity based on these effects. Therefore, we studied and explored the antiaging potential of exogenous hydrogen and its ability to extend longevity using Caenorhabditis elegans (C. elegans) as an animal model. Our results showed that the lifespans of the N2, sod-3 and sod-5 mutant strains were extended by approximately 22.7%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The positive correlation between longevity and microbial pathway MF0047: glutamine degradation II in both tongue dorsum (β = 0.551, p = 0.00098) and gut (β = 0.021, p = 0.00022) agreed with previous findings that glutamine-supplemented mice also showed remarkably a full one-third extension of lifespan 56 . Longevity was positively correlated with the gut microbial pathway hydrogen metabolism, which extends the lifespan of C. elegans by reducing reactive oxygen species 57 . Second, the lack of individual-level data prevented us from directly comparing the contributions of the microbiome and other host factors (economic/behavioral/environmental) to longevity.…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation between longevity and microbial pathway MF0047: glutamine degradation II in both tongue dorsum (β = 0.551, p = 0.00098) and gut (β = 0.021, p = 0.00022) agreed with previous findings that glutamine-supplemented mice also showed remarkably a full one-third extension of lifespan 56 . Longevity was positively correlated with the gut microbial pathway hydrogen metabolism, which extends the lifespan of C. elegans by reducing reactive oxygen species 57 . Second, the lack of individual-level data prevented us from directly comparing the contributions of the microbiome and other host factors (economic/behavioral/environmental) to longevity.…”
Section: Discussionmentioning
confidence: 99%
“…Steady-state ROS levels were measured by staining with the ROS-reactive dye DCFDA, and fluorescence (normalized to worm size) was measured using a Cytation5 Multi-Mode reader. DCFDA fluorescence is an efficient method for measuring ROS in C. elegans due to the permeability of the cuticle and minimal signal loss due to the transparency of the organism [68][69][70][71]. Three conditions, ego-2(RNAi), bar-1(RNAi), and pps-1(RNAi), showed increased ROS (Figure 5C).…”
Section: Disruption Of a Validation Subset Impairs Mitochondrial Func...mentioning
confidence: 99%
“…It is now considered a major factor underlying the development and progression of various diseases, such as COPD and idiopathic PF. Molecular hydrogen can decrease the expression of the aging-related proteins β-galactosidase, p53, and p21 (Han et al, 2017;Zhang WB et al, 2018), suppress downregulation of sirtuin 3 (Sirt3) expression, and reduce oxidative stress damage, thereby extending cell survival (Li et al, 2019;Zhang et al, 2020). Research has shown that molecular hydrogen produced by intestinal bacteria in the body suppresses increased hydrogen peroxide (H 2 O 2 ) by suppressing intracellular •OH-mediated lipid peroxide formation and cellular senescence, thus contributing to the suppression of aging (Sakai et al, 2019).…”
Section: Regulation Of Agingmentioning
confidence: 99%